THE ROLE AND PLACE OF NATIONAL HUMAN RIGHTS INSTITUTIONS IN THE PROMOTION AND PROTECTION OF HUMAN RIGHTS (ON THE EXAMPLE OF HUMAN RIGHTS INSTITUTIONS OF THE ORGANISATION OF ISLAMIC COOPERATION) (World Bulletin of Management and Law, 2024)
This scientific article analyzes the legal status of national human rights institutions of member states of the Organization of Islamic Cooperation (OIC), as well as their place and role in the protection and promotion of human rights at the global scale.
Keywords: Human rights; national human rights institutions; the United Nations